FARGOCPT: 2D multiphysics code for simulating disk interactions with stars, planets, and particles - Rometsch, Thomas; Jordan, Lucas M.; Moldenhauer, Tobias W.; Wehner, Dennis; Restrepo, Steven Rendon; Müller, Tobias W. A.; Picogna, Giovanni; Kley, Wilhelm; Dullemond, Cornelis (Astronomy and astrophysics, 2024)
Context: Planet-disk interactions play a crucial role in the understanding of planet formation and disk evolution. There are multiple numerical tools available to simulate these interactions, including the commonly used FARGO code and its variants. Many of the codes have been extended over time to include additional physical processes, with a focus on their accurate modeling. Aims: We introduce FARGOCPT, an updated version of FARGO that incorporates other previous enhancements to the code, to provide a simulation environment tailored to studies of the interactions between stars, planets, and disks. It is meant to ensure an accurate representation of planet systems, hydrodynamics, and dust dynamics, with a focus on usability.Methods: The radiation-hydrodynamics part of FARGOCPT uses a second-order upwind scheme in 2D polar coordinates, supporting multiple equations of state, radiation transport, heating and cooling, and self-gravity. Shocks are considered using artificial viscosity. The integration of the N-body system is achieved by leveraging the REBOUND code. The dust module utilizes massless tracer particles, adapted to drag laws for the Stokes and Epstein regimes. Moreover, FARGOCPT provides mechanisms to simulate accretion onto stars and planets. Results: The code has been tested in practice in the context of multiple studies. Additionally, it comes with an automated test suite for checking the physics modules. It is available online. Conclusions: FARGOCPT offers a unique set of simulation capabilities within the current landscape of publicly available planet-disk interaction simulation tools. Its structured interface and underlying technical updates are intended to assist researchers in ongoing explorations of planet formation.
Gesehen am 04.11.2024